1967
DOI: 10.1029/jz072i010p02595
|View full text |Cite
|
Sign up to set email alerts
|

Tripartite phase velocity observations in laterally heterogeneous regions

Abstract: The hypothesis that one can assign the phase velocity calculated, from a tripartite net to one of the legs of the net exclusively, when that leg approximately coincides with the surface wave propagation vector, has been substantiated by experimental data. If more than one leg of an array of stations is parallel to the propagation vector, it is possible to make a quantitative estimate of the lateral heterogeneity of structure across the net. If, however, the propagation vector coincides with only one of the leg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1972
1972
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 2 publications
0
14
0
Order By: Relevance
“…Earlier works have already been done to compute phase velocities and the approach azimuth of the wave train for a given period, by means of a triangular network [Evernden, 1954]. Although the tripartite phase velocity method was designed to handle surface waves incident upon the array from any azimuth, the results of Knopoff et al[1967] showed that when the direction of propagation does not lie along one of the legs of the network, the phase velocities computed may be in significant error. Schwab and Kausel [ 1976] proposed the extension to quadripartite networks to solve this limitation.…”
Section: Paper Number 93gl00774mentioning
confidence: 99%
“…Earlier works have already been done to compute phase velocities and the approach azimuth of the wave train for a given period, by means of a triangular network [Evernden, 1954]. Although the tripartite phase velocity method was designed to handle surface waves incident upon the array from any azimuth, the results of Knopoff et al[1967] showed that when the direction of propagation does not lie along one of the legs of the network, the phase velocities computed may be in significant error. Schwab and Kausel [ 1976] proposed the extension to quadripartite networks to solve this limitation.…”
Section: Paper Number 93gl00774mentioning
confidence: 99%
“…Stars and triangles show the location of earthquakes (NEIC 2003;ISC 2003) and of the seismic stations whose records are used for group-velocity measurements, respectively. Several stations and events are located outside of the shown region, but the location of all events and stations used for group-velocity measurements in the study area are listed in Tables 1 and 2, respectively The penetration depth of our dataset is increased considering, in addition, published phasevelocity measurements (Knopoff and Panza 1977;Panza 1981) for Rayleigh waves that span over the period range from about 15-20 to about 150 s. The phase-velocity measurements in the following studies are collected: Payo (1965Payo ( , 1969, Berry and Knopoff (1967), Knopoff et al (1967), Sprecher (1976), Marillier (1981), Marillier and Mueller (1985), Badal et al (1996), and Lana et al (1997).…”
Section: Methods and Datamentioning
confidence: 99%
“…Some of the earliest such measurements of phase velocity, for periods <1 s, can be found in the oil exploration literature (e.g., Dobrin et al, 1951). Knopoff et al (1967) later found the two-station method to be superior to the tripartite method to minimize errors in phase shifts in the presence of lateral heterogeneity. Press (1956Press ( , 1957 used the triangulation or tripartite method to determine crustal structure in California from average phase velocities.…”
Section: Phase Velocitymentioning
confidence: 99%